Air-thermal oxidation of zirconium - Zagorka Koneska; Ružica Manojlović; Dafinka Stoevska-Gogovska (Journal of Engineering & Processing Management, 2017)
Zirconium is one of those few metals which are capable of dissolving relativelylarge quantities of oxygen. When heated in air at elevated temperatures, anoxide layer is built up at the metal surface. The oxidation of mechanicallypolished zirconium was studied in the range 500-900 ℃ in air atmosphere, attemperature intervals of 100 ℃, for exposure times from 5 min to 1860 min foreach temperature. The weight gain of the oxidized species was the reactedamount of oxygen with zirconium for the formation of the ZrO2. The weight gainand thickness of the oxide film increase with the increasing of the oxidation timeand temperature. The oxidation initially followed a parabolic rate at alltemperatures. At temperatures higher than 700 ℃ oxide “breakaway” appears atthe longest oxidation times. Microstructural investigations have shown that theoxide layers are compact and with good adhesion to the metal surface, but attemperatures over 700 ℃, radial micro-cracks appear. Raman spectra of theformed oxides at the investigated temperatures are characteristic for monoclinicphase.
Keywords: corrosion; thermal oxidation; zirconium; ZrO2